Sustainable energy solutions for climate change - Diesendorf, Mark (Routledge, Taylor & Francis Group, 2014)
This book is a call to action on climate change, filled with clear and detailed information on the strategies we need to adopt to ensure a sustainable future for the planet. We have the technology needed to transform our fossil-fuel based energy systems into ecologically sustainable ones, and this book argues that all we now need is the political will to do so. It uniquely brings together both the science and policy issues to provide a truly interdisciplinary approach.